Problem-focused coping underlying lower caregiver burden in ALS-FTD: implications for caregiver intervention. Issue 5 (3rd July 2021) - Caga, Jashelle; Zoing, Margaret C.; Foxe, David; Ramsey, Eleanor; D'Mello, Mirelle; Mioshi, Eneida; Ahmed, Rebekah M.; Kiernan, Matthew C.; Piguet, Olivier
Abstract: Objective : Amyotrophic lateral sclerosis (ALS) is a multisystem neurodegenerative disorder which includes cognitive and behavioral symptoms akin to frontotemporal dementia (FTD). Despite the necessity of caregiver intervention to assist with the management of cognitive and behavioral symptoms, there has been a lack of research on the topic. A focus on caregiver coping may offer a promising foundation to guide the development of interventions as part of ALS care. Accordingly, the aim of the present study was to examine the relationships between caregiver coping, psychological morbidity and burden of care in the context of ALS cognitive and behavioral symptoms. Methods : Fifty-five patient-caregiver dyads were recruited from specialized ALS and FTD clinics. Specific coping strategies were examined using the COPE Inventory/Brief COPE and psychological morbidity and burden were assessed using the Depression, Anxiety, and Stress Scale–21 and Zarit Burden Interview. The relationship between coping, psychological morbidity and burden of care were analyzed using univariate and multivariate methods. Results : High-burden caregivers were more likely to be caring for patients with a diagnosis of ALS-FTD ( p =.0001). Caregivers used problem-focused strategies (particularly planning) more frequently ( M  = 71.4, SD = 15.3) compared to emotion-focused ( M  = 60.8, SD = 12.3) and dysfunctional coping strategies ( M  = 42.2, SD = 8.6). A diagnosis of ALS-FTD ( p =.0001) and problem-focused strategies ( p =.024) emerged as significant predictors of caregiver burden. Caregiver anxiety, depression and stress were not predictive of caregiver burden ( p =.151). Conclusions : Timely provision of caregiver support optimizing problem-focused coping strategies as part of multidisciplinary ALS care, particularly for caregivers of ALS-FTD patients may mitigate caregiver burden.